Serum Sodium Status in Children with Autism Spectrum Disorder (Sir Salimullah Medical College Journal, 2026)
Background: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder that may cause lifelong disability. Nutritional factor is related to the development and progression of autism spectrum disorder. The aim of the study was to assess minerals and trace elements play important role in brain development. Assess of serum sodium status in children with autism spectrum disorder. Method: This case control observational study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st January 2022 to 31st December 2022. For this study, a total number of sixty (60) children age ranged 5-10 years both male and female were included and divided into two groups. Cases were consisted of thirty (30) diagnosed ASD children and controls were consisted of from thirty (30) healthy children. Then the parents were requested to attend the Department of Biochemistry and Molecular Biology in Bangladesh Medical University(BMU) for collection of blood sample in scheduled dates.Serum sodium level was estimated in children of both groups. Statistical -analysis was done by using Statistical Package of Social Science (SPSS) for windows version 22. Unpaired “t” test was done to compare the data as applicable. p value d” 0.05 was considered as level of significance. Results: In this study, serum sodium level was lower in children with ASD than that of healthy children, but the level was statistically non-significant. Conclusion: Serum sodium level was lower in children with ASD.Sir Salimullah Med Coll J 2025; 33: 37-44